Open Admission’s Grade-Entry Requirements and Academic Performance in Junior High School: An Analysis - De Leon, Orlando Jr. (Future Science / FSH-PH Publications, 2022)
Private high-school admission procedures frequently involve testing prospective students to determine their eligibility for enrollment, but this changed because of the COVID-19 pandemic. Numerous schools were adversely affected by the situation. To survive the economic crisis and declining enrollment among schools, many private schools altered their admissions policies. Even admission test providers have switched to online testing with increased prices of two to three times. The introduction of open admission did away with the requirement for an entrance exam but required applicants to submit their grades from the previous two academic years, which served as a benchmark for their potential academic performance in the school. The researcher used this chance to conduct a descriptive-correlational study to determine whether the grade-entry requirements can accurately predict the learners' academic performance. The general averages of the respondents for the previous two academic years were correlated with their general averages for the current academic year, which served as a quantitative representation of their academic performance at the school where they were admitted. The learners' grade-entry requirements revealed a statistically significant relationship between those averages and their academic performance in the school. Furthermore, the school of origin and initial admission status, whether qualified or waitlisted, were also correlated with their general averages, and it was found that only the latter has a statistically significant relationship with academic performance. The researcher suggested that grade-entry requirements could already be used as a reliable indicator of the prospective academic performance of admission applicants, even without an admission test.